2010
DOI: 10.4081/ejh.2010.e36
|View full text |Cite
|
Sign up to set email alerts
|

Histochemical and morpho­metrical study of mouse intestine epithelium after a long term diet containing genetically modified soybean

Abstract: Diet can influence the structural characteristics of both small and large intestine. In this study, we investigated the duodenum and colon of mice fed on genetically modified (GM) soybean during their whole life span (1–24 months) by focusing our attention on the histological and ultrastructural characteristics of the epithelium, the histochemical pattern of goblet cell mucins, and the growth profile of the coliform population. Our results demonstrate that controls and GM-soybean fed mice are similarly affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Nonetheless, histochemical scrutiny disclosed significant dietrelated changes in amounts of the duodenum's mucin. In particular, the percentage of villous area occupied by acidic and sulpho-mucin granules decreased from controls to GM-fed animals, whereas neutral mucins did not change [18].…”
Section: In a Related Study Controls And 14% Gm-soybean Diet-expressingmentioning
confidence: 83%
See 1 more Smart Citation
“…Nonetheless, histochemical scrutiny disclosed significant dietrelated changes in amounts of the duodenum's mucin. In particular, the percentage of villous area occupied by acidic and sulpho-mucin granules decreased from controls to GM-fed animals, whereas neutral mucins did not change [18].…”
Section: In a Related Study Controls And 14% Gm-soybean Diet-expressingmentioning
confidence: 83%
“…CP4EPSPS gene conferring high level tolerance to glyphosate, fed mice were likewise affected by aging [18]. Comparably, long term feeding on GM soybean (1-24 months) did not induce structural alterations in duodenal and colonic epithelium or in coliform population.…”
Section: In a Related Study Controls And 14% Gm-soybean Diet-expressingmentioning
confidence: 91%
“…It also possesses phytochemicals, including isoflavones and phytate, which may contribute to the reduction of the risk factors of cardiovascular disease (CVD), type 2 diabetes mellitus and atherosclerosis [ 6 - 8 ]. However, it has been reported that soy, in addition to a balanced diet, changes the intestinal morphology, impairing the nutrient absorption in the small intestine [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…2327 Most of these studies were performed by light (essentially conventional or confocal fluorescence) microscopy, but electron microscopy and ultrastructural immunohistochemistry has also been used for investigating functional changes in cells from different tissues or under different experimental conditions. 2837 To localize specific nuclear components, multiple immunohistochemical techniques and quantitative analyses of the immunogold labelling have been utilized, 38 and this approach proved to be especially appropriate to detect the alteration in transcription and splicing which characterizes specific diseases. 24,31,39 …”
Section: A Survey Of the Recent Contents Of A Long-time Established Hmentioning
confidence: 99%